Aarachar - K. R. Meera (D.C. Books, 2012)
Aarachar--Executioner is a story based on the Indian culture of caste and religion. The story illustrated in Kolkata narrates about a family's culture and profession of "executioner" which was being performed by men from decades. Chetna, that's what the protagonist of the story called as, father was an executioner, a profession inherited by him. But today, there is no one to inherit this profession... Will a girl, Chetna, be able to inherit her family profession of Execution? The book "Aarachar" by K R Meera tells the story of such a girl.